A linkage map of cassava (Manihot esculenta Crantz) based on RFLP and RAPD markers - Fregene, Martin A.; Angel, F.; Gómez, R.; Rodríguez, F.; Maya, M.M.; Bonierbale, Merideth W.; Tohme, Joseph M.; Iglesias, C.A. (International Center for Tropical Agriculture, 1995)
A preliminary linkage map of cassava (Manihot esculenta Crantz) to increase the efficiency of introgression of specific chromosomes or chromosome fragments from exotic cassava germplasm into various genetic backgrounds and localization of genes of interest in cassava improvement schemes has been drawn from F1 segregation data of single-dose polymorphisms of RFLP and RAPD markers. The mapping effort involves a population of 90 plants derived from a cross between two elite cassava lines-MNg2 (TMS 30572), possessing resistance to the African cassava mosaic virus (ACMV) disease, and CM 2177-2 (ICA-Cebucán), possessing high photosynthetic rates. The map comprises over 200 loci corresponding to genomic clones selected from Pstl, Hindill and EcoRI random genomic libraries (RFLP markers) and polymorphisms from arbitrarily primed polymerase chain reaction (RAPD markers). Of about 900 random genomic clones detected RFLPs between the two parental cultivars. Tests of linkage between segregating RFLP and RAPD markers, with respect to the male parent (CM 2177-2) were conducted using the MAPMAKER computer package. Segregation of the markers revealed a predominantly disomic mode of inheritance in cassava, otherwise thought to be an allopolyploid. Efforts continue to saturate the map and develop genetic stocks with segregating traits of interest to obtain tightly linked markers to these traits is being carried out. A scheme to tag useful genes in cassava such as known sources of the ACMV resistance genes is presented